Effects of Prenatal Dexamethasone on the Rat Pituitary Gland and Gonadotropic Cells in Female Offspring - Ristić, Nataša; Severs, Walter; Nestorović, Nataša; Jarić, Ivana; Manojlović-Stojanoski, Milica; Trifunović, Svetlana; Pendovski, Lazo; Milosević, Verica (S. Karger AG, 2016)
Glucocorticoids have a strong influence on growth and maturation of fetal organ systems, but overexposure to exogenous glucocorticoids may retard fetal growth and alter developmental processes in sensitive tissues. The aim of this study was to specifically determine whether prenatal exposure to dexamethasone (Dx) altered normal development and function of pituitary gonadotropic cells in neonatal, infant and peripubertal female offspring. On day 16 of pregnancy, rat dams received 1.0 mg Dx/kg body weight (BW) s.c., followed by 0.5 mg Dx/kg BW on days 17 and 18 of gestation. Control gravid females received the same volume of saline. Female offspring were sacrificed on days 5, 16 and 38 after delivery. The volume of the pituitary gland estimated using Cavalieri's principle was significantly reduced (p < 0.05). Using a fractionator-physical disector method, we found reduced total numbers of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) cells (p < 0.05), accompanied by a decrease (p < 0.05) in serum concentrations of FSH and LH, while the relative intensity of FSH and LH immunofluorescence remained unchanged in neonatal, infant and peripubertal female offspring prenatally exposed to Dx. The data document that overexposure to Dx during fetal development evokes developmental programming of the female reproductive system at the pituitary cellular level, which may be associated with impaired reproductive function.